Policy approaches to advancing food safety: aligning culture with science for behavior change in Bangladesh - Rock, Christine (Kansas State University, 2021)
Policies, formal or informal, can be determinants of the effectiveness of any organization, no matter how big or small. Formal policies can take the form of primary laws or secondary regulations, while informal policies may only apply on the honor of individuals, businesses, or societies. Throughout history, food safety policies have evolved from isolated experiences of trial and error to standardized, scientific method-driven approaches. Still, the burden of foodborne disease remains a global concern, and governments often maintain the responsibility of curbing the deleterious effects. The policy decisions made to i) train food safety professionals, ii) educate producers and consumers on food-safe handling practices, and iii) conduct outreach activities can mean the difference between sickness and health in constituencies. In Bangladesh, these three policy priorities are led by the Bangladesh Food Safety Authority (BFSA). As a human-driven system, improving food safety requires behavior change. Policymakers can implement mechanisms for behavior change through their understanding of the national culture. Leaders should not use this information to exploit or manipulate but rather to embrace cultural nuance and share resonate messaging. Religion, specifically the Islamic faith, is a dominant cultural element in Bangladesh. Recognizing the connection between Muslim food laws—called Halal food laws and derived from Islamic text—and food safety is essential to writing effective food safety policies. An estimated 150 million Muslims live in Bangladesh and presumably abide by Halal food laws. Though many of the Halal principles of good hygiene and wholesomeness align with safe food production and consumption practices, high rates of foodborne disease persist. This research aims to i) describe the global history of governance around food safety, ii) outline existing international approaches to food safety, iii) discuss current theories of behavior change, iv) assess the capacity of the government of Bangladesh to improve food safety practices and outcomes, and v) evaluate the results and policy applications of the Food Safety Culture Assessment. The hypothesis of the Food Safety Culture Assessment is that there are observable patterns in food safety-related values, opinions, and perceptions, particularly as it relates to the cultural element of religion. The most apparent patterns were the significance respondents placed on faith, handwashing, partiality to taste over other factors of food selection, and the value of women and healthcare providers in food safety information dissemination. These resources were developed to inform policy decisions and build capacity at the Bangladesh Food Safety Authority (BFSA). As the BFSA establishes itself to be the proper authority on food safety issues, it will be well-served to align national culture considerations like the Islamic faith with data-driven, scientific findings when working to improve food safety policy.
Keywords: Food safety; Behavior change